2013
DOI: 10.1111/j.1469-0691.2012.03993.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Echinococcus granulosus in south-eastern Romania: evidence of G1–G3 and G6–G10 complexes in humans

Abstract: Echinococcus granulosus is the aetiological agent of cystic echinococcosis (CE), which is a public health problem in many eastern European countries, particularly in Romania, where the infection causes a high number of human and animal cases. To shed light on the transmission patterns of the parasite, we performed a genotyping analysis on 60 cyst samples obtained from patients who live in south-eastern Romania and who underwent surgery for liver or lung CE. DNA was extracted from the endocysts or the cyst flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
2
29
1
1
Order By: Relevance
“…The finding of E. granulosus s.s. in these patients is in agreement with previous studies which provided evidence of almost all human CE records in Romania infected with this species [25][26][27]. However, in a survey by Piccoli et al [28] a single human case of E. canadensis G7 was reported, apart from 59 cases of E. granulosus s.s. in patients from south-eastern Romania. The authors stated that the main risk factor for acquiring CE infection seemed to be the close contact with stray dogs reported for 97% of patients.…”
Section: Discussionsupporting
confidence: 69%
“…The finding of E. granulosus s.s. in these patients is in agreement with previous studies which provided evidence of almost all human CE records in Romania infected with this species [25][26][27]. However, in a survey by Piccoli et al [28] a single human case of E. canadensis G7 was reported, apart from 59 cases of E. granulosus s.s. in patients from south-eastern Romania. The authors stated that the main risk factor for acquiring CE infection seemed to be the close contact with stray dogs reported for 97% of patients.…”
Section: Discussionsupporting
confidence: 69%
“…[48][49][50][51][52][53][54][55] For the first time in Iran, Sharbatkhori and others 30 reported the occurrence of the G3 genotype in camels from the Isfahan Province (central Iran). This was a global first for the identification of the G3 genotype in this host.…”
Section: Discussionmentioning
confidence: 99%
“…29 Globally, many studies identified the G1 genotype as the most common or the only genotype causing human CE, whereas the G6 genotype has indicated no or low infectivity to humans. 55,[57][58][59][60][61] However, the G1 and G6 genotypes of E. granulosus genotypes are most commonly associated with human infection worldwide and in Iran. Table 4 summarizes the identification of the G6 genotype in humans across the world.…”
Section: Discussionmentioning
confidence: 99%
“…According to official data from the National Centre of Infectious and Parasitic Diseases, the average incidence of the disease was steady (4.45/10 5 inhabitants) in the years 2009e14 (Muhtarov, 2014;Piccoli et al, 2013). p1245…”
Section: U N C O R R E C T E D P R O O F S0390 3453 Cystic Echinocmentioning
confidence: 99%